Environmentally Friendly Educational Innovation Tool To Recognize Numbers from Inorganic Waste - Agatha, Melinda Yulia; Najib, Ainun; Avanda, Pretty Aura Natasya; Latifah, Lafifatul; Ana, Selvia Roos (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Inorganic waste is a significant environmental problem due to population growth and rapid industrial development. The ever-increasing volume of inorganic waste demands effective solutions for its management. One way to reduce the negative impact of inorganic waste is to recycle it into useful items. In Lumajang Regency, there is an urgent need for learning facilities for early childhood children which are still inadequate. For this reason, innovation in the form of educational teaching aids (APE) from recycled inorganic waste materials has been developed. This APE not only helps overcome environmental problems but also provides practical solutions to improve the quality of children's education. This program aims to increase children's creativity, support educational facilities and infrastructure, and create interactive and fun learning. The methods used in implementing the program involve socialization, trials of making APE, training for teachers, mentoring, and monitoring activities. The results show that partners (teachers) are able to operate and apply educational game tools in learning, thus having a positive impact on children's cognitive and motor development. Keywords : Inorganic Waste, Environmental Problems, Recycling, Educational Teaching Aids, Early Childhood Education, Interactive Learning.